Deeply and vertically etched butte structure of vertical GaN p–n diode with avalanche capability. (28th May 2019) - Fukushima, Hayata; Usami, Shigeyoshi; Ogura, Masaya; Ando, Yuto; Tanaka, Atsushi; Deki, Manato; Kushimoto, Maki; Nitta, Shugo; Honda, Yoshio; Amano, Hiroshi
Abstract: A vertical p–n diode with a simple edge termination structure on a GaN free-standing substrate is demonstrated. The edge of this device is terminated simply by etching a drift layer deeply and vertically. A device simulation revealed that the electric field at the device edge was more relaxed and uniformly applied by etching the mesa deeper than the depletion region. The fabricated device showed low leakage current and avalanche capability, and its breakdown characteristics could be reproduced many times. By emission microscopy observation, we found that there was no leakage current at the side wall of the device and that avalanche breakdown occurred throughout the inside of the device. This indicates that the electric field crowding at the side wall of the device was completely suppressed and a uniform electric field distribution was obtained by this structure.